Improving the organizational and economic aspects of the development of Kazakh education in the field of tourism - Zhanakova, N.N.; Tolepov, A.Y.; Shayakhmetova, L.M.; Nurgliyeva, Z.H.; Kabiyeva, A.T. (BUKETOV BUSINESS REVIEW, 2024)
Object: To study the current state of development of Kazakhstani education in tourism and identify problems in the preparedness and provision of the Kazakh labor market with professional personnel in this field. Methods: the method of content analysis of documents, covering statistical analysis and processing of the current situation in the field of tourism education was used. The conducted research is based on the institutional method, the systematic method, the method of relative assessment, the method of general scientific generalization. In the article foresight tools of the tourism of Kazakhstan were used. Findings: During the scientific study a critical reduction in the number of students by the beginning of the 2022- 2023 academic year was revealed, which may lead to a shortage of personnel in the tourism, the consequences of which the Kazakh labor market will feel in a few years. The main reason for the decrease in the number of students is a sharp reduction by the authorized body in the education sphere in the number of grants allocated for training in educational programs of tourism specialties. Educational programs in tourism do not fully meet the real needs of the industry due to their low focus on practical work, as a result of which the personnel of specialized tourism specialties remain unclaimed. Conclusions: In the Kazakh education system, it is necessary to develop related types of professions in the tourism industry, taking into account the needs of the modern market of tourist services. The requirements for teachers of educational institutions should be aimed at improving the quality of education with a focus on the practical application of the courses taught; collaboration of authorized organizations in the field of education and tourism is important.